PENGGUNAAN KOMIK KESEHATAN GIGI DALAM MENINGKATKAN PENGETAHUAN DAN KEPERCAYAAN SISWA KELAS V SDN MARTOPURO 01 KECAMATAN PURWOSARI KABUPATEN PASURUAN - Zuhriyyatul Haq (Universitas Airlangga, 2015)
Dental health problem in Indonesia, according to RISKESDAS data 2013, was 25.9% of total population. About 68.9% of them didn’t get treatment from medical personnel and about 25.5% of them were on age 10 to 14. This was the reason why the comic that belong to Health Campaign Central of Indonesian Ministry of Health was used as media of dental health problem campaign. This study was done with questionnaire fulfi llment that conducted by 40 students of SDN Martopuro 01 Kecamatan Purwosari Kabupaten Purwodadi. This study used Quasi Experimental Design. The result of this study describe there was a signifi cant difference between pre-test and post-test score on knowledge variable. This meant that comic about dental health problem which gave to respondent could improve their knowledge. From the belief variable measurement, there was no signifi cant difference between pre-test and post-test score of belief variable, in other way the dental health comic which gave to respondent didn’t improve their belief. Respondent assessed that the content of comic was accurate and fit. This study concluded that comic belonged to Health Campaign Central of Indonesian Ministry of Health could improve the knowledge of fifth grade students of SDN Martopuro, Kecamatan Purwosari KabupatenPasuruan about dental health.Keywords: dental health comic, knowledge, behavior belief